2017
DOI: 10.1016/j.gdata.2017.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Mannose-Binding Lectin ( MBL ) gene polymorphisms in susceptibility to pulmonary tuberculosis among the Lur population of Lorestan Province of Iran

Abstract: ObjectiveTuberculosis (TB) is caused by infection of Mycobacterium tuberculosis. Host genetic variability is an important determinant of the risk of developing TB in humans. Although the association between MBL polymorphisms and TB has been studied in various populations, the results are controversial. The aim of this study was to investigate mannose-binding lectin (MBL) gene polymorphisms with susceptibility to pulmonary tuberculosis (PTB) in a Lur population of Iran.MethodsIn this case-control study, four fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 56 publications
(79 reference statements)
0
10
0
Order By: Relevance
“…Li et al (2018) in a study on Chinese Uygur population found that MBL2 rs7095891 polymorphism was associated with an increased risk of TB; however, they did not find any association between rs1800450 as well as rs7096206 polymorphism and tuberculosis. Meanwhile, many studies have not found any association between MBL2 rs1800450 polymorphism and susceptibility or protection to tuberculosis (Soborg et al, 2007;Araújo et al, 2013;da Cruz et al, 2013;Wu et al, 2015;Amiri et al, 2017). The effect of MBL level on TB susceptibility has been controversial.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Li et al (2018) in a study on Chinese Uygur population found that MBL2 rs7095891 polymorphism was associated with an increased risk of TB; however, they did not find any association between rs1800450 as well as rs7096206 polymorphism and tuberculosis. Meanwhile, many studies have not found any association between MBL2 rs1800450 polymorphism and susceptibility or protection to tuberculosis (Soborg et al, 2007;Araújo et al, 2013;da Cruz et al, 2013;Wu et al, 2015;Amiri et al, 2017). The effect of MBL level on TB susceptibility has been controversial.…”
Section: Resultsmentioning
confidence: 99%
“…These polymorphisms changed the structure of MBL proteins causing a functional deficiency and reduction of stability; as such they were more rapidly degraded and thus reduced the serum level of MBL (Heitzeneder et al, 2012;Mandal et al, 2019). Also, it seems that these MBL proteins have less binding capacity to mannose and cannot activate complement via the lectin pathway (Amiri et al, 2017). However, Thye et al (2011) showed higher levels of MBL can promote infection by increasing the uptake of intracellular pathogens by phagocytes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to this day, a wide spectrum of other methods have been used for detection of MBL2 gene variants, including commercially available TaqMan assays [ 27 ], high-resolution melt analysis (HRMA) [ 28 ], reverse hybridization with membrane-immobilized sequence-specific oligonucleotide probes (reverse PCR-SSOP) [ 29 ], PCR with sequence-specific primers (SSP-PCR) [ 30 , 31 ], PCR and restriction-fragment length polymorphism (PCR-RFLP) analysis [ 32 ], an oligonucleotide ligation assay [ 33 , 34 ], a single-strand conformation polymorphism technique (PCR-SSCP) [ 35 ], the iPLEX assay on a MassArray system [ 36 ], Sanger sequencing [ 37 ], and pyrosequencing [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, LYPB haplotype showed a significant association with increased risk of TB among Chinese population ( 225 ). Whereas, in Iranian Lur population MBL H allele and HH genotype significantly associated with increased susceptibility to TB ( 226 ).…”
Section: Genetic Variants and Tb Associationmentioning
confidence: 99%